EFISIENSI BIAYA PRODUKSI DAN DAYA SAING KOMODITI PERIKANAN LAUT DI PASAR LOKAL DAN PASAR EKSPOR - Onu La Ola (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2014)
Each company will try to improve the efficiency of production costs, the competitiveness of production in conducting production and transaction of fish commodity in the local and export market. Objective: (1) assess the level of efficiency costs of production and marketing fish commodities in the local market and export markets every month; (2) assess the competitiveness of commodity fish in the local market and export markets every month. The study found that: (1) the level of cost-efficient production and marketing of fish commodities in the local market and export markets are found in the process of production and marketing in the export market in October-November amounted to Rp3.451.861 / kg (2) The highest of Competitiveness of fish commodities is in the export market in November 2012 amounted to Rp11.548/ kg and the rate of increase of competitiveness in the export market by 9.48%/month.